2021
DOI: 10.1051/e3sconf/202131403005
|View full text |Cite
|
Sign up to set email alerts
|

KPCA over PCA to assess urban resilience to floods

Abstract: Global increases in the occurrence and frequency of flood have highlighted the need for resilience approaches to deal with future floods. The principal component analysis (PCA) has been used widely to understand the resilience of the urban system to floods. Based on feature extraction and dimensionality reduction, the PCA reduces datasets to representations consisting of principal components. Kernel PCA (KPCA) is the nonlinear form of PCA, which efficiently presents a complicated data in a lower dimensional sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In linear PCA, the data is projected onto a linear subspace of lower dimensions (Han et al, 2011). But linear PCA does not perform well when the data is linearly non‐separable (Satour et al, 2021).…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In linear PCA, the data is projected onto a linear subspace of lower dimensions (Han et al, 2011). But linear PCA does not perform well when the data is linearly non‐separable (Satour et al, 2021).…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Dimensionality reduction analysis for improving the performance of tweet‐level stress detection is not addressed in the literature (KVTKN & Ramakrishnudu, 2022; Lin et al, 2016; Lin et al, 2017; Lin, Jia, Guo, Xue, Huang, et al, 2014; Pratama & Sarno, 2015; Xue et al, 2016; Zhao et al, 2015). It is observed that Kernel Principal Component Analysis (PCA) helps in obtaining the dimensionality reduction when the classes are linearly non‐separable (Satour et al, 2021). The reasons for choosing PCA over other dimensionality reduction methods are listed as follows: There are many dimensionality reduction techniques that rely on the use of classifiers, such as forward selection, chi‐square, backward selection, and so forth.…”
Section: Introductionmentioning
confidence: 99%